1983
DOI: 10.1080/01652176.1983.9693887
|View full text |Cite
|
Sign up to set email alerts
|

Clinical papers

Abstract: SUMMARY In a commercial swine herd a rise was noted during the summer of 1981 in the number of repeat breeders, mostly four to eight weeks after serving. During the autumn there was a decrease in the litter size at birth and an increase in the number of stillborn and mummified piglets. Several gilts and sows showed a seroconversion against Porcine Parvovirus (PPV), determined by the Haemagglutination Inhibition lest (HI-test). Characteristic pathologicalfindings were seen in some maturely stillborn and neonata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…It is interesting to note that, in samples from aborted pig fetuses collected in Beijing, only PPV6 was detected. Targeted studies are needed to investigate the role of this virus in the sows with reproductive failure [ 2 ]. However, the number of clinical samples detected in this study was limited and more extensive epidemiologic studies are needed to elucidate the precise role of PPV6 as a causal agent for reproductive failure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that, in samples from aborted pig fetuses collected in Beijing, only PPV6 was detected. Targeted studies are needed to investigate the role of this virus in the sows with reproductive failure [ 2 ]. However, the number of clinical samples detected in this study was limited and more extensive epidemiologic studies are needed to elucidate the precise role of PPV6 as a causal agent for reproductive failure.…”
Section: Resultsmentioning
confidence: 99%
“…Porcine parvoviruses (PPV) are important pathogens that cause reproductive failure in swine, resulting in enormous losses in the pig industry worldwide [ 1 ]. Epidemiological studies and diagnostic surveys have demonstrated that PPV was the major causative agent responsible for embryonic and fetal death in swine [ 2 ]. Parvoviruses are classified into two subfamilies based on their host range: the Parvovirinae , which infect vertebrates, and the Densovirinae , which mainly infect insects and other arthropods.…”
Section: Introductionmentioning
confidence: 99%
“…The parvoviruses are small, non-enveloped, single-stranded DNA viruses. PPV is a major cause of reproductive failure in sows and is a significant cofactor in porcine postweaning multisystemic wasting syndrome [1][2][3]. PPV was first isolated from pigs with fever in 1965 [4].…”
Section: Introductionmentioning
confidence: 99%
“…PPV was first isolated from pigs with fever in 1965 [4]. It is commonly found in diseased pigs and is the cause of significant economic loss for the swine industry today [1,[5][6][7][8][9]. Currently, vaccination is the primary measure for prevention of PPV.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the Parvovirinae subfamily are among the most dangerous and economically most harmful viruses of domesticated and farm animals (e.g., canine parvovirus (CPV) [16], goose parvovirus (GPV) [17] porcine parvovirus (PPV) [18] and are also able to cause diseases in humans (B19) [19] and human bocavirus [20,21]. PPV is responsible for syndrome of reproductive failure in swine, included infertility, early embryonic death, mummified fetuses and stillbirths [22].…”
Section: Introductionmentioning
confidence: 99%